Synthesis, magnetic properties and enhanced photoluminescence of Fe3O4-ZnO heterostructure multifunctional nanoparticles - Dung, Chu Tien; Quynh, Luu Manh; Hong, Tran Thi; Nam, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics, 2017)
Abstract. In this paper, Fe 3 O 4 -ZnO heterostructure multifunctional nanoparticles (NPs) were successfully prepared in aqueous solution by ultrasound assisted thermolysis. First, iron oxide (Fe 3 O 4 ) magnetic NPs were prepared by co-precipitation method. The Fe 3 O 4 NPs were modified by 3-aminopropyltriethoxysilane (APTES) to have free amine (-NH 2 ) groups on their surface, then, Zn 2+ ions were added and stirred to adsorb onto the surface of Fe 3 O 4 -NH 2 NPs in alkaline solution at a pH of 11. This solution was decomposed through thermolysis in ultrasound bath. The results of measurements show that photoluminescence of Fe 3 O 4 -ZnO heterostructure multifunctional NPs was enhanced in visible light at 565 nm wavelength to allow detection, labeling, diagnosis, and therapy in biomedicine. Moreover, they exhibit superparamagnetic properties of Fe 3 O 4 with high saturation magnetization ( M S ), which can be used for seperation application in biomedicine under an external magnetic field. Keywords. Fe 3 O 4 -ZnO, multifunctional nanoparticles, heterostructure, enhanced photoluminescence